Adsorption of betacyanin on yarns - Nurul Ain, Ibrahim (2015)
In textile industry, synthetic colourant is widely used as it is much cheaper and has high stability but the use of synthetic dye poses a great concern and threat to the environment when discharged. Thus, to overcome the problem, natural colourant is introduced as a substitute to synthetic colourant. Peel of Hylocereus polyrhizus or red-purple fleshed dragon fruits could be an attractive and potential source of red colourant for textile industry as the peel possess high content of betacyanin. Despite the potential, as a natural colourant, betacyanin cannot adheres well with certain types of fabric. This study provides determination of suitable yarns to be dyed with dragon fruit peel. Betacyanin was extracted from dragon fruit peel by simple water extraction at 100°C and adsorption process was carried out by soaking polyester cotton, rayon, and rayon coolmax yarns into stock solution for optimum time at 90 minutes. Langmuir and Freundlich isotherm models were applied in order to describe the equilibrium at different parameters and isotherm constants. Root mean square error and chi square analysis were used to test the models’ goodness of fit by non-linear regression due to the bias in using the correlation coefficient resulting from linearization. Freundlich model gave the best result for the adsorption isotherm. The applicability of Freundlich isotherm model showed the heterogeneous adsorption surface with sites have different energies of adsorption as the Freundlich model assumes. The result also have demonstrated the potency of dragon fruit peel as a source of natural colouring agents for dyeing of yarns by conventional techniques and perhaps more advanced techniques.